Detenction and characterization of stone fruit virus diseases in Tunisia - Boulila, Mohamed (Phytopathologia Mediterranea, 2001)
A preliminary survey was conducted in Tunisia to identify stone fruit (almond, plum, peach) virus diseases occurring in orchards and mother block stands. Two ilarviruses, Prunus necrotic ringspot virus (PNRSV) and Prune dwarf virus (PDV) infecting almond and plum and a trichovirus, Apple chlorotic leaf spot virus (ACLSV) found in a peach orchard in northern Tunisia, were detected. These viruses were detected by means of herbaceous and woody indicators (cucumber, peach GF 305), serology (DAS-ELISA), electron microscopy (DIP, ISEM, Decoration) and reverse transcription-polymerase chain reaction-based assay (RT-PCR). Furthermore, typing PNRSV isolates was done by bioassays using various species and cultivars of Cucurbitaceae, serotyping with specific monoclonal antibodies (Mabs) in ELISA-DASI and RFLP analysis. Characterization work showed that serotyping with Mabs was the best mean to distinguish between PNRSV isolates.